Conceptualising and testing the Narnian Character Virtue Scales: a study among 12- to 13-year-old students. Issue 9 (21st October 2017) - Francis, Leslie J.; Pike, Mark; Lankshear, David W.; Nesfield, Victoria; Lickona, Thomas
ABSTRACT: This paper sets out to examine and to operationalise 12 key character virtues identified within C. S. Lewis' Narnian texts: courage, curiosity, forgiveness, fortitude, gratitude, hard work, humility, integrity, justice, love, self-control, and wisdom. A pilot study among 56 year eight students (12–13 years of age) generated nine five-item instruments displaying adequate internal consistency reliability, and suggested ways in which the other three measures (curiosity, integrity, and love) could be enhanced in future work. Construct validity was explored by examining the correlations between these 12 character virtues and sex, self-concept, and empathy, and by locating these 12 character virtues within the three-dimensional psychological space proposed by Eysenck's model of personality.